Pengembangan Keterampilan Ecoprint Pada Media Keramik Untuk Mendukung Usaha Ekowisata di Rhepang Muaif Nimbokrang, Kabupaten Jayapura - Ohee, Henderite L.; Warikar, Evie L.; Ramandey, Euniche R.P.F. (Jurusan Biologi FMIPA Universitas Cenderawasih, 2024)
Ecotourism in Rhepang Muaif Village is increasingly widely known by local and foreign tourists. The high awareness of nature conservation by the Rhepang Muaif Village Community is one of the important values for protecting the forest. However, based on the results of discussions with several managers that they need other alternative sources of income based on local wisdom. The purpose of this activity is to make ecoprinting training for managers and communities in Rhepang Muaif Village, Nimbokrang, Jayapura-Papua and practice directly making ecoprints for managers and communities in Rhepang Muaif Village, Nimbokrang, Jayapura-Papua. The training was conducted in August 2023, involving 16 participants. The training provided included material on the definition of ecoprint, its benefits, basic materials / ecoprint media, what types of leaves or flowers are used, what techniques can be used and the steps for making ecoprints on ceramic media. After the participants followed the demonstration on ecoprint, the service activity continued with practice on ceramic mugs and plates. The results of the ecoprint work have very diverse motifs with natural colors from leaves and flowers that are very beautiful. Participants looked very satisfied and happy because they could express their creativity and imagination in an environmentally friendly work. The enthusiasm of the participants in participating in this training activity was very high. This indicates that the service participants positively welcomed the activities that had been carried out.